Dietary N‐Nitroso Compounds and Risk of Hepatocellular Carcinoma: A USA‐Based Study. Issue 6 (26th August 2021) - Zheng, Jiali; Daniel, Carrie R.; Hatia, Rikita I.; Stuff, Janice; Abdelhakeem, Ahmed A.; Rashid, Asif; Chun, Yun Shin; Jalal, Prasun K.; Kaseb, Ahmed O.; Li, Donghui; Hassan, Manal M.
Abstract : Background and Aims: N‐nitroso compounds (NOCs) are among the most potent dietary carcinogens. N‐nitrosodiethylamine (NDEA), N‐nitrosodimethylamine (NDMA), and N‐nitrosopiperidine (NPIP) are abundant in foods and carcinogenic to the liver. We investigated the relationship between dietary NOCs and HCC risk. Approach and Results: In this large, hospital‐based, case‐control study of 827 pathologically or radiologically confirmed HCC cases and 1, 013 controls, NOC intake was calculated by linking food frequency questionnaire–derived dietary data with a comprehensive NOC concentration database. Multivariable‐adjusted ORs and 95% CIs of HCC by quartiles of NOC consumption were estimated using logistic regression models, with the lowest quartile as the referent. We further investigated joint effects of consuming the highest quartile of NOCs that were associated with increased HCC risk and hepatitis, diabetes, or alcohol drinking on HCC risk. After adjustment for confounding factors, higher intake of NDEA from plant sources (ORQ4 vs. Q1  = 1.58; 95% CI = 1.03‐2.41), NDMA from plant sources (ORQ4 vs. Q1  = 1.54; 95% CI = 1.01‐2.34), and NPIP (ORQ4 vs. Q1  = 2.52; 95% CI = 1.62‐3.94) was associated with increased HCC risk. No association was observed for nitrate or total NOC intake and HCC risk. Higher consumption of HCC‐inducing NOCs and positive hepatitis virus status jointly increased the risk of developing HCC. Conclusions: In conclusion, though some of our findings may indicate the presence of reverse causation owing to lower meat intake among cases with chronic liver diseases before HCC diagnosis, the potent dietary HCC carcinogens, NDEA, NDMA, and NPIP, and their enhanced carcinogenic effects among chronic carriers of hepatitis virus warrant further prospective investigation.